Identification of Maleo (Macrocephalon Maleo) and Gosong Kaki Merah (Megapodius Reindwardt) DNA Similarity Level Using Needleman-Wunsch Algorithm - Rusmi, Rusmi; Ratianingsih, Rina; Najar, Abdul Mahatir (Syiah Kuala University, 2023)
Sequence Alignment is used to find out the similarity of the sequence of two DNA. One of the alignment algorithms is the Needleman-Wunsch algorithm which is a global alignment algorithm that uses the entire length of the DNA sequence. In this research, the algorithm is applied to a website-based application system to determine the level of similarity of the DNA sequence of Maleo (Macrocephalon Maleo) which is an endemic animal to Sulawesi, with a comparison of Gosong Kaki Merah (Megapodius Reinwardt) which has a wide global distribution. The results of the alignment of Maleo (Macrocephalon Maleo) and Kaki Merah (Megapodius Reinwardt) DNA sequences on a website-based application system have an average similarity level of 83.39% and an average gap value of 8.42%.